Representações sociais de DST/AIDS para adolescentes de uma instituição abrigo com experiência pregressa de vida nas ruas da cidade de Goiânia - BORGES, Ida Kuroki (2004)
Adolescents in street situation likely exposed to STD/AIDS because the street world is favorable for violence use and traffic of drugs sexual exploration and also they had difficulties to assimilate information about this subject and to access health services These aspects had been discussed from the knowledge produced by health and social sciences about the sexuality vulnerability and exposition for the STD/AIDS of sheltered adolescents with previous life experience in the streets In this study we sough to identify and to analyze the social representations of prevention DST/AIDS for a group of adolescents with experience of life in the streets living in a shelter institution in Goiânia Goiás Brazil This inquiry has been based on social approach of qualitative research in health which social representations as methodological principle The data was collected by in-depth interview with a group of sheltered adolescents of both genres and diary-field notes from participant observations and analyzed by thematic modality of the content analysis As results we identified three thematic categories: omnipotence and finite prevention and risks bodies changes the knowledge of STD/AIDS to the adolescents prevention and sexuality in order to we verify that AIDS is better known among them than other STD In their understanding AIDS appears as incurable disease leading to death Although they know about risks they do not adopt a prevention behavior The risk factors are linked to their own powerful beliefs ignorance use of inject able drugs or others and difficulties to get condoms makes that diminishes the risks perceptions threshold and consequently also their protection attitudes The knowledge about sexuality is restricted to the physical and biological modifications not knowing exactly what is happening with their body in each phase of their physical affective sexual and social development Considering the irregularity that initiates their sexual life time some limitations to preventing their selves against STD appears These results allow us to consider about our responsibility to extending our activities beyond the limits of Academy and thus contributing to Public Policy elaboration through accords with governmental and non-governmental organizations by a community effort to propose effective projects of interventions for this population still unknown for great part of the society inside of its historical context